A concise review on advances in development of small molecule anti-inflammatory therapeutics emphasising AMPK: An emerging target. (December 2016) - Gejjalagere Honnappa, Chethan; Mazhuvancherry Kesavan, Unnikrishnan
Inflammatory diseases are complex, multi-factorial outcomes of evolutionarily conserved tissue repair processes. For decades, non-steroidal anti-inflammatory drugs and cyclooxygenase inhibitors, the primary drugs of choice for the management of inflammatory diseases, addressed individual targets in the arachidonic acid pathway. Unsatisfactory safety and efficacy profiles of the above have necessitated the development of multi-target agents to treat complex inflammatory diseases. Current anti-inflammatory therapies still fall short of clinical needs and the clinical trial results of multi-target therapeutics are anticipated. Additionally, new drug targets are emerging with improved understanding of molecular mechanisms controlling the pathophysiology of inflammation. This review presents an outline of small molecules and drug targets in anti-inflammatory therapeutics with a summary of a newly identified target AMP-activated protein kinase, which constitutes a novel therapeutic pathway in inflammatory pathology.